Flood risk reduction and resilient city growth in sub-Saharan Africa: searching for coherence in Accra's urban planning - Oteng-Ababio, Martin; Agergaard, Jytte; Møller-Jensen, Lasse; Andreasen, Manja H. (Frontiers in Sustainable Cities, 2024)
Urban resilience experts have highlighted that frequent extreme weather events result from rapid, unplanned development and climate change. Effective land governance has been a priority since the introduction of the national urban policy in 2012 to ensure coherent urban planning. However, despite implementing this policy for over a decade, poor land governance continues to impact city development negatively, yet this subject has received limited academic attention. Our study focuses on Santa Maria, a community historically neglected by planning officials and currently facing unregulated urbanisation and increasing flood risks. We used qualitative research methods to unpack land ownership and management complexities, including key informant interviews and document reviews. These complexities have led to "planning by the commons," the creation of green space deserts, and challenges related to residents' mobility and livelihood. Our study affirms that auto-constructed communities like Santa Maria reflect a form of tenacious urbanism that should be acknowledged and respected. Incorporating its logic into proposals for consolidation, informed by the opinions and desires of the residents themselves, can help integrate "planning by the commons" into Accra's urban planning process. Rather than being viewed as a problem to be cured, this approach should be incorporated into the planning process, incorporating locally specific social functions and traditional structures to ensure equitable and just urban societies. The public sector must recognise that building on local capacity, skills, and expertise is essential in the quest for a resilient city. The experience from Santa Maria provides an excellent opportunity to nurture local development, fulfil the growing demand for solutions and services without biases, and provide an excellent opportunity for inclusive growth.